Computerized Banking Operations and Internal Financial Control Practices - Mutia Hawa; Baiq Vilda Resky Aulia; Sari Ratna Kumala Putri Singgih; Aliyah Ardiastri; Siska Febrianty; Restu Alpiansah (Lentera Pengabdian, 2026)
Internship programs play an important role in equipping students with practical competencies relevant to professional work environments. This study used a descriptive qualitative case study design based on one month of direct observation and active participation conducted from February 2 to March 2, 2026 by two undergraduate Management Study Program students at Bank Rakyat Indonesia Ampenan Unit, with the teller and administrative sections as the unit of analysis. Data were drawn from daily activity logs, field observation notes, and banking administrative documentation, and were analyzed descriptively to identify recurring control practices. This article aims to describe banking operational activities and analyze how internal financial control systems were implemented to support operational effectiveness during the internship period. The findings show that verifying transaction documents against recorded data at the AATR archive helped ensure consistency between documentation and actual customer transactions, while the storage of loan and collateral documents in designated, code-referenced archives at BRIMEN reflected a safeguarding practice intended to protect sensitive customer records. These findings suggest that routine, entry-level administrative tasks in banking operations embed concrete internal control practices that can serve as practical reference points for strengthening branch-level control environments and for structuring future student internship placements.